Selecting a mentor: guide for a Protégé - Memon, Jamshed; Abd Rozan, Zaidi; Uddin, Mueen; Shah, Asadullah; , Dzurllkanian (IDOSI Publication, 2013)
The development of entrepreneurial skills within the education system increases the possibility of producing more entrepreneurs in future. Many economists now believe that entrepreneurship plays an important role in economic growth of a country. Entrepreneurial education can be used as a mediation tool for impacting attitude of people towards entrepreneurship.A Mentor plays an important role in entrepreneurial development of an individual. It is a mentor who guide entrepreneur from conception of business to product development and business growth, but in order to provide mentoring a mentor need to have certain qualities and a proven track record. Select the right mentor is most important because a mentor who is incompatible with entrepreneur’s personality or requirement may cost entrepreneur the whole business. This research puts a light on subjective and objective qualities a mentor should possess and will provide a guideline to protégé regarding selection of appropriate mentor.